Application of Adomian decomposition method to solving some kinds of partial differential equations and system of partial differential equations - Loufouilou, Justin Mouyedo; Bissanga, Gabriel; Francis, Bassono; PARE, Youssouf (International Journal of Advanced Mathematical Sciences, 2013)
In this article, the Adomian decomposition method (ADM) is used to construct the solution of the initial value problem of some kinds of partial differential equations of first order.